Large-scale annotation of biomedical data and expert label synthesis and hardware aware learning for medical imaging and computer assisted intervention : International Workshops, LABELS 2019, HAL-MICCAI 2019, and CuRIOUS 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 13 and 17, 2019, proceedings /: International Workshops, LABELS 2019, HAL-MICCAI 2019, and CuRIOUS 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 13 and 17, 2019, proceedings. (2020) - Unknown
No abstract available